Manufaktur Spacer Dengan Dimensi 180 X 150 X 30mm Pada Blangking Die - Achmad Fauzan (Universitas Gajah Putih, 2021)
The spacer is a part of the die that functions as a foundation or support at the top and bottom of the die to prevent deformation. The process of making this spacer requires 4 stages of work, namely: surface grinding, drilling, milling, tapping. with the material used in making the spacer is S50C carbon steel. The steel was chosen because it has high wear-resistant material properties and dynamic loads. After that, the first stage is smoothing the surface of the material with a surface grinding process which is carried out automatically for ± 8 minutes. Then the next step is to make holes with the drilling process with sizes 12, 7, 5, and 3.5 mm, these holes are used to insert pillars and bolts so that they blend with the other parts. The third stage is the milling process to remove the middle part with a box shape of 112mm x 91mm according to the design. Then the last stage is the tapping process to make a thread using an m4 drill bit.